Influence of Education, Health Complaints, Dependence, and Family Support on The Work Participation of the Population Elderly Age in Denpasar City - Mohammad Saif Al-Moreno; Ni Nyoman Reni Suasih (International Journal of Management Research and Economics, 2024)
The ever-increasing life expectancy rate has shown that there has been economic progress, environmental improvements and advances in science, especially due to advances in medical science. The higher life expectancy shows the increasing number of elderly people, which of course will influence the increase in the absorption of elderly labor itself. The aim of this research is to analyze the influence of education, health complaints, number of dependents, and family support simultaneously and partially on the work participation of the elderly population in Denpasar City. In this study, the number of samples taken was 100 elderly people from 69,323 elderly people in Denpasar City. The sampling method used was a non-probability sampling method with a purposive sampling technique combined with accidental sampling. The data analysis techniques used are descriptive statistical analysis test, classical assumption test, multiple linear regression analysis test, F test and t test. The research results show that education, health complaints, number of dependents, and family support simultaneously and significantly influence the work participation of the elderly population in Denpasar City. Education, number of dependents, and family support partially have a positive and significant effect on the work participation of the elderly population in Denpasar City, while health complaints partially have a negative and significant effect on the work participation of the elderly population in the City of Denpasar.